The analysis of participant activity in utilizing the Integrated Post for Non-Communicable Disease Empowerment Services (Posbindu PTM) - Siregar, Tanti Alarma; Herlina; Rahmad Gurusinga (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background: Non-communicable diseases (NCDs) are the leading cause of death globally, including in Indonesia. Although the Posbindu PTM program has been implemented for early detection of NCD risk factors, public participation remains low. This raises questions about the factors influencing participants' activity in utilizing this service at Puskesmas Bintang Bayu.Objective: This study aims to analyze the factors influencing participants' activity in utilizing the Posbindu PTM service at Puskesmas Bintang Bayu, focusing on predispositional, enabling, and reinforcing factors. Research Method: A quantitative approach with an analytic survey design was used. Data was collected through questionnaires and interviews with Posbindu PTM participants at Puskesmas Bintang Bayu and analyzed using descriptive statistics and logistic regression Results: Participants' activity was influenced by age, knowledge, and healthcare worker support. Older participants tend to be more active, and good knowledge, along with support from healthcare workers and family, also increases participation. Major barriers include work commitments and limited accessibility. Conclusion: Good knowledge and social support are dominant factors influencing participants' activity. Intensive education and improvements in accessibility and infrastructure are necessary to increase public participation in Posbindu PTM.